2019
DOI: 10.5498/wjp.v9.i3.47
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for using pimavanserin for the treatment of Parkinson's disease psychosis

Abstract: The aim of this editorial is to evaluate the evidence for using pimavanserin for the treatment of Parkinson's disease psychosis (PDP) from randomized controlled trials (RCTs). We only identified two published trials that evaluated the use of pimavanserin among individuals with PDP. Both studies found that pimavanserin improved psychotic symptoms among individuals with PDP when compared to placebo. Pimavanserin was fairly well tolerated in both studies and did not appear to cause significant sedation or worsen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, this did not translate into clinical efficacy. Nevertheless, another 5-HT 2 receptor antagonist, primavanserin, has shown efficacy in the treatment of psychosis associated with Parkinson’s disease (Tampi et al 2019 ) and was approved by the FDA for the treatment of hallucination and delusions associated this condition. This could be seen as an illustration of the benefits of adopting an RDoC approach.…”
Section: Principle 8: Learn and Reflectmentioning
confidence: 99%
“…However, this did not translate into clinical efficacy. Nevertheless, another 5-HT 2 receptor antagonist, primavanserin, has shown efficacy in the treatment of psychosis associated with Parkinson’s disease (Tampi et al 2019 ) and was approved by the FDA for the treatment of hallucination and delusions associated this condition. This could be seen as an illustration of the benefits of adopting an RDoC approach.…”
Section: Principle 8: Learn and Reflectmentioning
confidence: 99%
“…It’s also important to note that the impact and maximal benefit is not immediate and studies have shown that response is noted after 2-6 weeks of therapy. 27 The side effect profile of pimavanserin is QTc prolongation and increased risk of associated cardiac arrhythmia. 27 Another consideration for pimavanserin use is the FDA black box warning given findings of post-surveillance studies demonstrating an increased risk of death that is similar to other antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…83 Pimavanserin has been demonstrated to be effective in many studies. 84,85 Cummings et al conducted a randomized, double-blinded, placebo-controlled phase III trial (n=199) and showed that pimavanserin resulted in a statistically significant improvement in scores for positive psychotic symptoms, with no significant motor symptom worsening. 84 Tampi et al reviewed this and one other randomized, placebo-controlled double-blinded study and showed that 80.5% of individuals treated with pimavanserin experienced at least some improvement in symptoms compared with 58.1% of individuals who received a placebo (n=259).…”
Section: Treatment Approaches For Parkinson's Disease Psychosismentioning
confidence: 99%
“…84 Tampi et al reviewed this and one other randomized, placebo-controlled double-blinded study and showed that 80.5% of individuals treated with pimavanserin experienced at least some improvement in symptoms compared with 58.1% of individuals who received a placebo (n=259). 85 Despite demonstrated efficacy, the drug's high cost serves as a barrier to many patients. 65 Additionally, pimavanserin should be avoided in patients with severe cardiac and/or hepatic or renal impairment (creatinine clearance <30 mL/min), as it is metabolized by CYP3A4 and CYP3A5 and may result in QTc prolongation.…”
Section: Treatment Approaches For Parkinson's Disease Psychosismentioning
confidence: 99%